Głosy z przeszłości: mikrohistoryczne narracje Hou Hsiao-hsiena - Loska, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The focus of the text is on the representation of Taiwanese history in two films by Hou Hsiao-hsien, City of Sadness (Beiqing chengshi, 1989) and Good Men, Good Women (Hao nan hao nu, 1995), which refer to the traumatic events of February and March 1947. Both works were conceived as a protest against the official version of history, and at the same time as a reminder of what the authorities tried to erase from the public sphere. The director did not intend to simply reconstruct the past, but to create an experimental narrative by reaching out to those whose testimonies were usually ignored. Hou Hsiao-hsien adopted a view typical of microhistory, in which it is important to consider an individual perspective, i.e., to present human lives and the everyday activities. His films convince us that the process of learning about history does not rely solely on the use of scientific methods, but occurs due to the work of imagination, because – as Ewa Domańska writes – “we believe in history in the same way as we believe in works of art which speak to us not through cold logic, but by influencing our aesthetic and emotional sensitivity.”